Treatment of Aggressive NK-Cell Leukemia: A Case Report and Review of the Literature - Boysen, Anders Kindberg; Jensen, Paw; Johansen, Preben; Dybkær, Karen; Nyegaard, Mette (Case Reports in Hematology, 2011)
Aggressive NK-cell leukemia is a rare malignancy with neoplastic proliferation of natural killer cells. It often presents with constitutional symptoms, a rapid declining clinical course, and a poor prognosis with a median survival of a few months. The disease is usually resistant to cytotoxic agents, and no treatment has emerged as the standard of care for these patients. We report a case of an 18-year-old male who obtains complete remission following two lines of combination chemotherapy. We describe in details our regimens for induction chemotherapy and perform a review of existing literature concerning treatment of aggressive NK-cell leukemia.